Sexualité et régime de normativité à l’âge confessionnel - Jean-Pascal Gay (Cahiers d’histoire.)
This text proposes a macroscopic analysis of the relationship of Catholicism to sexuality the confessional era. It also tries to account for the contemporary focus of Catholic morality on the issue of sexuality. This focus cannot be understood simply as an accident or as the result of the politicization of public discussions of sex. It reveals a structure still at work in modern-day Catholicism. It results on the one hand from the typically confessional increase in normative pressure on bodies and consciences, but also on the other hand from a change in the locus of normativity. The transition towards a regime of intense individual religious performances certainly contributed to the growing anxiety over sex as a moral issue. Therefore, the early modern focalization on sex reveals the contradictory dynamics of Catholic confessionalization. It weakens the very normative order it builds at the very same time that it builds it. Contemporary conflict between Catholics, the societies they live in, and the new legal order of sexuality appears as evidence of the preserved strength of confessional culture in contemporary Catholicism despite its profound recent transformations.